User acceptance of enterprise resource planning systems: a study in small and medium enterprises in Vietnam - Le, Thi Minh Duc (International Journal of Entrepreneurship and Innovation Management, 2021)
International Journal of Entrepreneurship and Innovation Management, 2021 Vol.25 No.1, pp.72 - 104